Do differences exist between chronic hepatitis C genotypes 2 and 3? - Isaura Cunha Melo; Maria Lucia Gomes Ferraz; Renata Mello Perez; Christine Takemi Emori; Silvia Naomi de Oliveira Uehara; Roberto José de Carvalho-Filho; Antonio Eduardo Benedito Silva; Ivonete Sandra de Souza e Silva (Revista da Sociedade Brasileira de Medicina Tropical)
Introduction Six genotypes of the hepatitis C virus (HCV) have been identified thus far, and their distribution is well defined. Genotype 1, which is the most prevalent worldwide, is always compared to genotypes 2 and 3, particularly in terms of treatment response. However, little is known about the differences between genotypes 2 and 3 because these genotypes are analyzed together in most studies. Therefore, the aim of this study was to evaluate differences in the clinical, epidemiological, laboratory, and histological parameters between HCV-2 and HCV-3. Methods Patients with chronic hepatitis C infected with genotypes 2 and 3 were studied retrospectively and compared according to clinical, laboratory, and histological aspects. Hepatitis C virus-ribonucleic acid (HCV-RNA) was analyzed quantitatively by TaqMan® real-time PCR, and the HCV genotype was determined by sequencing the 5′-untranslated region. Results A total of 306 patients with chronic HCV-2 (n=50) and HCV-3 (n = 256) were studied. Subtype 2b (n=17/50) and subtype 3a (n=244/256) were the most prevalent among patients infected with HCV-2 and HCV-3, respectively. The mean age was 47 ± 10 years, and there was a predominance of men in the group studied (61%). Comparative analysis between HCV-2 and HCV-3 showed a younger age (p=0.002), less prevalence of arterial hypertension (p=0.03), higher serum albumin levels (p=0.01), more advanced stage of liver fibrosis (p=0.03), and higher frequency of steatosis in patients with HCV-3 (p=0.001). After multivariate regression analysis, all the variables, except serum albumin, remained as variables associated with HCV-3 in the final model. Conclusions Clinical and histological differences exist between HCV-2 and HVC-3, which suggests the need for separate analyses of these genotypes.